The efficacy and safety of upadacitinib treatment for moderate to severe atopic dermatitis in real‐world practice in Japan. Issue 11 (19th August 2022) - Hagino, Teppei; Saeki, Hidehisa; Kanda, Naoko
Abstract: We evaluated the efficacy and safety of upadacitinib, janus kinase 1 inhibitor for atopic dermatitis (AD) in real‐world practice. From September 2021 to March 2022, 31 patients with moderate‐to‐severe AD, aged ≥12 years were treated with oral upadacitinib 15 mg/day plus topical corticosteroids. Upadacitinib reduced clinical indexes compared to baseline levels: percent reduction at week 4 and 12 (median) was 73.6% and 85.6% in eczema area and severity index (EASI); 81.3% and 81.3% in AD control tool (ADCT); and 70% and 75% in peak pruritus numerical rating score (PP‐NRS), respectively. The achievement rate of EASI 75 was 51.6% and 67.7% at week 4 and 12, respectively. Upadacitinib reduced serum lactate dehydrogenase and total eosinophil count (TEC) at week 4 and 12, and thymus and activation‐regulated chemokine and immunoglobulin E at week 4, compared to baseline levels. Percent reduction of TEC was correlated with that of EASI at week 4 and 12. Baseline TEC was positively correlated with the percent reduction of EASI at week 4. Percent reduction of EASI in female patients was higher than that in male patients at week 4 and 12. Linear multivariate regression analyses revealed that high percent reduction of EASI at week 4 or 12 was associated with high baseline TEC or female gender, respectively. There were no serious treatment‐emergent adverse events. Adverse events include acne (5%), elevation of creatine phosphokinase (9.7%), herpes zoster (1%), and AD (1%). Upadacitinib plus topical corticosteroids for patients with AD in the real‐world practice was well tolerated and gave therapeutic effects comparable with those in previous clinical trials. The ADCT and PP‐NRS rapidly reduced at week 4 while EASI gradually reduced until week 12. The TEC might act both as a predictive factor of response at week 4 and as a biomarker reflecting therapeutic effects in upadacitinib treatment for AD.